Theoretical foundations of forming value orientation of pupils by means of school sports abroad - Turchyk, I.Kh. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to determine the theoretical basis for the formation of value orientations of pupils by means of school sports facilities abroad. Material: detailed analysis of 14 published sources. Results: found that in a foreign academic and journalistic literature dominates positive appreciation of cultural values of humanistic school sports in the formation of value orientations of pupils. Found that school sport abroad plays an important role not only as a means of forming the basic values - health, but also an important area of communication, the manifestations of social activity. As well as physical and mental form of organization and leisure facilities, excellent vehicle impacts on other values of human life: the authority and position in society, work, the structure of moral and volitional characteristics, aesthetic ideals and other value orientations. Conclusions: confirmed that the global experience of formation values pupil means school sports deserves attention and requires selective introduction into the domestic education system.